Avaliação experimental e numérica de uniões parafusadas de aços ARBL furadas por escoamento - Fripp, William Haubert (2017)
In the work carried out, a theoretical study was carried out to validate a structural analysis model using the finite element method, in a screwed union made of tubes of high resistance and low alloy USI-LN 700 steels, and to identify possible influences in the HAZ caused by the flow drilling process, in the results of tensions and life in fatigue. The study was based on mapping characteristics of the material supplied, to verify if the thermal input caused by the flow drilling influences the properties of the material. The machining parameters were pre-defined and then the bodies were subjected to tensile (screw start) and fatigue tests. This led to the description of the model proposed in the study with the aid of the ANSYS Software, and later the results of the practical tests were compared with those of the analyzes in order to validate the model proposed by the study. It was possible to identify through the metallography a change in the microstructure of the material, which resulted in a reduction of the mechanical strength as shown by the profile of microhardness traced. It was not possible to conclude if the proposed model is efficient when we talk about the traction on the screw or if there is influence of the process in the results. In the fatigue, the results were more conclusive, where the model withstand 11000 cycles compared to the 12500 cycles resulting from the tests, not presenting clear process influences for the proposed model.